Reformulation, text modeling, and the development of EFL academic writing - Sulistyo, Teguh; Heriyawati, Dwi Fita (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2017)
This paper mainly investigates the benefits of the implementation of Reformulation and Text Modelling in an EFL writing setting. Reformulation and Text Modeling (henceforth RTM) is intended to help EFL students understand better how to write academic texts to make their texts sound as nativelike as possible. Therefore, RTM was implemented in a writing class in which 35 students participated as the respondents of the study. They were treated with RTM and their essays were then analyzed to examine the effects of the implementation of RTM on their writing products. Besides, this study investigated further the studentsâ perception towards RTM in EFL writing settings. The findings of this study proved that RTM is beneficial to improve studentsâ writing performances and students have positive perceptions on RTM. The implications of the findings for language learning are also discussed.